Impact of promoting blood donation in general practice: Prospective study among blood donors in France - Renaux, Ophélie; Bouazzi, Leila; Sanchez, Antoine; Hottois, Judith; Martin, Marie-Charlotte; Chrusciel, Jan; Sanchez, Stéphane (Frontiers in Public Health, 2022)
Introduction: Waiting rooms in general practitioners’ (GP) surgeries are a potentially useful site for spreading educational messages about health behaviors. We aimed to evaluate the impact of posters displayed in GPs’ waiting rooms on the number of donors attending the blood donation drives in the Aube Department of France. The secondary objective was to identify self-reported factors that incited people to give blood among donors who did and donors who did not see the posters. Methods: Observational, multicenter, prospective study, from 1 June to 31 December 2021. Six blood donation centers in the Aube Department were selected. All GPs located within a 15km radius around each center were invited to participate by hanging posters advertising blood drives in their waiting rooms. The number of blood donations per hour was measured before and during the campaign. Factors prompting people to give blood were evaluated by questionnaires completed by persons attending the blood drives. Results: 33 GPs participated. The number of donations per hour was lower in the year in which the posters were displayed (2021) compared to the previous year (12 versus 15). A total of 1469 questionnaires were completed by blood donors: 729 reported having seen the posters, and 740 reported not having seen the posters. Those who claimed to have seen the posters were more likely than those who claimed not to have seen the posters to respond that in parallel, they had been prompted to give blood via online publicity (7.5% vs 3.9%, adjusted Odds ratio [aOR] 1.75, 95% confidence interval [CI] 1.12-2.82, p=0.02). They also more often reported that they had been prompted to donate by television advertisements (8.0% vs 4.2%, aOR 1.74, 95%CI 1.10-2.76, p=0.02). Overall, 68% of all respondents indicated that posters in the GP’s waiting room would incite them to give blood more often. Conclusion: The number of blood donations per hour was lower during the year in which posters were displayed. Questionnaire data from donors suggests that promoting blood donation via posters in GPs’ waiting rooms could have a positive effect: 68% of donors claimed that posters would incite them to give blood.